JENIS UPAYA, SARANA PRASARANA, DAN KETERLIBATAN INSTANSI DALAM PENGENDALIAN FAKTOR RISIKO LEPTOSPIROSIS DI KOTA SEMARANG - Maknunah Setyowati; M. Sakundarno Adi; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Leptospirosis caused by infection leptospira bacteria, attacking animals and human. Leptospirosis disease is influenced by three main factors: host, agent, and an environment. Leptospirosis cases may rise during heavy rainfall and the environment that many puddles, like the city of Semarang. The purpose of this study to describe the prevention of risk factors leptospirosis in the city of Semarang. This type of research is descriptive qualitative with interview method. The research sample as many as 37 Primary Health Care and 1 Health Department, using total sampling technique. The results showed that all surveillance officer in Primary Health Care implement prevention risk factors for leptospirosis is counseling. Most of the Primary Health Care in Semarang City has a diagnostic tool is RDT and tools to catch rats is live trap. All surveillance officers in Semarang City collaboration with stakeholder region and health organization when there are cases of leptospirosis. It is advisable to health Department in order to distribute tool catching mice and RDT to all Primary Health Care.